PENGARUH PENGGUNAAN MEDIA PG2L MELALUI MODEL DIRECT INSTRUCTION TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PERSAMAAN GARIS LURUS - Muhdar Muhdar (Jurnal Kependidikan, 2018)
This paper is the result of an experimental study on the effectiveness of media Cork Board Linear Graph (CBLG) to the motivation and learning of mathematics in the matter straight line equation. Design research using experimental class and control class. The results of this study indicate that the use of media CBLG through direct instruction model of a positive effect on motivation and learning mathematics in particular the equation of a straight line material. This is shown by the average classroom of learning motivation. Average of motivation of the experiment class was 85,16, the control class was 77.21. Based on the analysis of the results of learning gains between pretest and posttest in the experimental classes obtained an average gain of 0.60 and the normalized derived control class average normalized gain of 0.47. The difference in the average motivation to learn and gain an average of the results of learning mathematics between the experimental class and the control class were tested using ttest formula. The results of t-test analysis (Levene's test) was concluded that there are significant differences in motivation and learning outcomes between the classes that use CBLG media through direct instruction models (experimental class) with a class that simply applying the model direct instruction (class control )